Glaciers as Climate-Driven Systems (Part I): Ein Beitrag zur komplexen Beziehung zwischen Hochgebirgsgletschern und klimatischen Einflussfaktoren als Beispiel einer systemischen Raumsachverhaltsbetrachtung im Geographieunterricht (Teil I) - Winkler, Stefan (Journal of Geography Education, 2004)
Natural systems are rather complex. However, it is important to understand the interactions and causal connections within such systems as mountain glaciers. The variable influence of climate factors on glacier behaviour is among the key issues of past and present global change. In this paper, a brief introduction of glaciology focussed on mass balance is followed by information on the mechanism of glacier front position changes. Glaciers are primarily presented as complex systems and elements of geoecosystems in high mountain regions. The second part shows ways to transform this subject for geography lessons. Accompanied with some general considerations, specific case examples clarifying the complex nature of the system ’glacier’ are given. Along follow addition experiments and figures suggested to be used if ’glaciers’ are made subject of lessons or projects within geography at school level.